Characterization of α-glucosidase inhibitors from clinacanthus nutans lindau Llaves by gas chromatography-mass spectrometry-based metabolomics and molecular docking simulation - Murugesu, Suganya; Ibrahim, Zalikha; Ahmed, Qamar Uddin; Nik Yusoff, Nik Mohd. Idris; Uzir, Bisha Fathamah; Perumal, Vikneswari; Abas, Faridah; Saari, Khozirah; El-Seedi, Hesham; Khatib, Alfi (MDPI, 2018)
Background: Clinacanthus nutans (C. nutans) is an Acanthaceae herbal shrub traditionally consumed to treat various diseases including diabetes in Malaysia. This study was designed to evaluate the α-glucosidase inhibitory activity of C. nutans leaves extracts, and to identify the metabolites responsible for the bioactivity. Methods: Crude extract obtained from the dried leaves using 80% methanolic solution was further partitioned using different polarity solvents. The resultant extracts were investigated for their α-glucosidase inhibitory potential followed by metabolites proﬁling using the gas chromatography tandem with mass spectrometry (GC-MS). Results: Multivariate data analysis was developed by correlating the bioactivity, and GC-MS data generated a suitable partial least square (PLS) model resulting in 11 bioactive compounds, namely, palmitic acid, phytol, hexadecanoic acid (methyl ester), 1-monopalmitin, stigmast-5-ene, pentadecanoic acid, heptadecanoic acid, 1-linolenoylglycerol, glycerol monostearate, alpha-tocospiro B, and stigmasterol. In-silico study via molecular docking was carried out using the crystal structure Saccharomyces cerevisiae isomaltase (PDB code: 3A4A). Interactions between the inhibitors and the protein were predicted involving residues, namely LYS156, THR310, PRO312, LEU313, GLU411, and ASN415 with hydrogen bond, while PHE314 and ARG315 with hydrophobic bonding. Conclusion: The study provides informative data on the potential α-glucosidase inhibitors identiﬁed in C. nutans leaves, indicating the plant’s therapeutic effect to manage hyperglycemia.